Recruiting and managing volunteers in museums : a handbook for volunteer management - Van Hoven, Kristy, 1983-; Wellman, Loni, 1981- (American Association for State and Local History book series., 2016)
We are in the middle of a museum paradigm shift and a new type of museum volunteer is emerging from the community. Non-profit volunteers are looking for unique and satisfying ways to engage in their communities and museums are primed to offer just the experiences these volunteers are looking for. Here's a practical exploration of the differences between the "then" and "now" volunteers and solid advice on volunteer recruitment, communication, and retention strategies. Written in a light hearted spirit, Recruiting and Managing Volunteers in Museums: A Handbook to Volunteer Management will engage.